Pachymic acid alleviates circadian rhythm disorders in high-fat diet-induced obesity mice via the sphingolipid pathway - Hong Yang; Yingxiu Mei; Jilan Chen; Jiawei Chen; Jiushuang Zhu; Lu Zhang; Yanju Gong; Gan Luo; Weijun Ding (PLoS ONE, 2026)
Background Obesity caused by a high-fat diet (HFD) is known to disrupt metabolic homeostasis and circadian rhythms. Pachymic acid (PA), a bioactive triterpenoid, exhibits anti-inflammatory, antihyperglycemic, antihyperlipidemic, and sedative-hypnotic properties, though its role in circadian regulation remains unexplored. Methods We assessed PA’s impact on metabolic dysfunction (glucose/lipid profiles), systemic inflammation using biochemical assays, ELISA, Oil Red O staining. Circadian parameters were evaluated via 24-h serum melatonin and core body temperature. Hepatic circadian gene oscillations and mechanistic pathways were analyzed through time-series RNA sequencing, bioinformatics, qPCR, and Western blotting. Results PA intervention attenuated obesity-related phenotypes, including reduced body weight, improved glucose/lipid metabolism, and restored physiological rhythms of melatonin and body temperature. And hepatic gene oscillation patterns were realigned to circadian synchrony. Mechanistically, PA ameliorated liver inflammation by modulating the sphingolipid pathway, specifically via S1PR4/TRAF2 signaling. Conclusions Our findings illustrate PA’s role in mitigating metabolic and circadian disruptions in obesity, highlighting the sphingolipid pathway as a tissue-specific target for circadian modulation. This study provides novel insights into therapeutic strategies for obesity-associated circadian disorders.